2016
DOI: 10.1038/srep36915
|View full text |Cite
|
Sign up to set email alerts
|

SAV742, a Novel AraC-Family Regulator from Streptomyces avermitilis, Controls Avermectin Biosynthesis, Cell Growth and Development

Abstract: Avermectins are useful anthelmintic antibiotics produced by Streptomyces avermitilis. We demonstrated that a novel AraC-family transcriptional regulator in this species, SAV742, is a global regulator that negatively controls avermectin biosynthesis and cell growth, but positively controls morphological differentiation. Deletion of its gene, sav_742, increased avermectin production and dry cell weight, but caused delayed formation of aerial hyphae and spores. SAV742 directly inhibited avermectin production by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…To elucidate the negative effect of AdpA Sx on morphological differentiation in S. xiamenensis 318, a multiple sequence alignment of AdpA homologues was performed. The result revealed that the amino acid sequence of AdpA Sx was highly similar to that of the well-studied AdpA (approximately 73%) except SVA742 (16%), which regulates secondary metabolite biosynthesis and morphological differentiation in S. avermitilis (25). Two conserved domains were detected in the alignment, a type 1 glutamine amidotransferase (GATase1) domain in the N terminus and a helix-turn-helix (HTH) DNA-binding domain, of the AraC family regulators, in the C terminus ( Fig.…”
Section: Resultsmentioning
confidence: 73%
“…To elucidate the negative effect of AdpA Sx on morphological differentiation in S. xiamenensis 318, a multiple sequence alignment of AdpA homologues was performed. The result revealed that the amino acid sequence of AdpA Sx was highly similar to that of the well-studied AdpA (approximately 73%) except SVA742 (16%), which regulates secondary metabolite biosynthesis and morphological differentiation in S. avermitilis (25). Two conserved domains were detected in the alignment, a type 1 glutamine amidotransferase (GATase1) domain in the N terminus and a helix-turn-helix (HTH) DNA-binding domain, of the AraC family regulators, in the C terminus ( Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Two single mutants of Sputcn32_0304 and Sputcn32_0305, Δ0304 and Δ0305, were constructed. The deletion mutant of Sputcn32_0304 was constructed according to previous studies (39)(40)(41), which can avoid the polar effect on expression of the downstream gene Sputcn32_0303 and facilitate the investigation on its own expression changes. The biofilm biomasses of both single mutants were significantly increased compared to that of the WT strain, and biofilms of both complementation strains C-0304 and C-0305 were restored to the WT level ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All other deletion mutants were constructed according to previous studies (39)(40)(41). To construct the Δ0304 mutant, PCR was used to generate a 1,587-bp DNA fragment upstream (positions Ϫ1443 to 144 relative to the Sputcn32_0304 start codon) and a 1,529-bp DNA fragment downstream (positions 565 to 2094 relative to the Sputcn32_0304 start codon) of the Sputcn32_0304 gene (reserving 144 bp after the start codon for real-time RT-PCR analysis) using primers 0304-5F/0304-5R and 0304-3F/0304-3R, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, spores and mycelia of S. roseosporus strains grown on DA1 plates for 2, 4, or 6 days were observed by SEM. Preparation and examination of samples were performed as described previously (Sun et al , ).…”
Section: Methodsmentioning
confidence: 99%